Chromosome alignment‐maintaining phosphoprotein CHAMP1 plays a role in cell survival through regulating Mcl‐1 expression. Issue 9 (16th July 2021) - Hino, Maho; Iemura, Kenji; Ikeda, Masanori; Itoh, Go; Tanaka, Kozo
Abstract: Antimitotic drugs such as vinca alkaloids and taxanes cause mitotic cell death after prolonged mitotic arrest. However, a fraction of cells escape from mitotic arrest by undergoing mitotic slippage, which is related to resistance to antimitotic drugs. Tipping the balance to mitotic cell death thus can be a way to overcome the drug resistance. Here we found that depletion of a mitotic regulator, CHAMP1 (chromosome alignment‐maintaining phosphoprotein, CAMP), accelerates the timing of mitotic cell death after mitotic arrest. Live cell imaging revealed that CHAMP1‐depleted cells died earlier than mock‐treated cells in the presence of antimitotic drugs that resulted in the reduction of cells undergoing mitotic slippage. Depletion CHAMP1 reduces the expression of antiapoptotic Bcl‐2 family proteins, especially Mcl‐1. We found that CHAMP1 maintains Mcl‐1 expression both at protein and mRNA levels independently of the cell cycle. At the protein level, CHAMP1 maintains Mcl‐1 stability by suppressing proteasome‐dependent degradation. Depletion of CHAMP1 reduces cell viability, and exhibits synergistic effects with antimitotic drugs. Our data suggest that CHAMP1 plays a role in the maintenance of Mcl‐1 expression, implying that CHAMP1 can be a target to overcome the resistance to antimitotic drugs. Abstract : We found that depletion of chromosome alignment‐maintaining phosphoprotein CHAMP1, a mitotic regulator, accelerates the timing of mitotic cell death in the presence of antimitotic drugs. CHAMP1 maintains expression of Mcl‐1, an antiapoptotic Bcl‐2 family protein, both at protein and mRNA levels. CHAMP1 depletion suppresses tumor growth in a xenograft model, and reduces cell viability synergistically with antimitotic drugs, implying that CHAMP1 can be a target to overcome drug resistance.